Topological quantum properties of chiral crystals. Issue 11 (November 2018) - Chang, Guoqing; Wieder, Benjamin; Schindler, Frank; Sanchez, Daniel; Belopolski, Ilya; Huang, Shin-Ming; Singh, Bahadur; Wu, Di; Chang, Tay-Rong; Neupert, Titus; Xu, Su-Yang; Lin, Hsin; et al.
Abstract Chiral crystals are materials with a lattice structure that has a well-defined handedness due to the lack of inversion, mirror or other roto-inversion symmetries. Although it has been shown that the presence of crystalline symmetries can protect topological band crossings, the topological electronic properties of chiral crystals remain largely uncharacterized. Here we show that Kramers–Weyl fermions are a universal topological electronic property of all non-magnetic chiral crystals with spin–orbit coupling and are guaranteed by structural chirality, lattice translation and time-reversal symmetry. Unlike conventional Weyl fermions, they appear at time-reversal-invariant momenta. We identify representative chiral materials in 33 of the 65 chiral space groups in which Kramers–Weyl fermions are relevant to the low-energy physics. We determine that all point-like nodal degeneracies in non-magnetic chiral crystals with relevant spin–orbit coupling carry non-trivial Chern numbers. Kramers–Weyl materials can exhibit a monopole-like electron spin texture and topologically non-trivial bulk Fermi surfaces over an unusually large energy window. Kramers–Weyl fermions are identified in chiral crystals, and their phenomenology is drawn out.